Prevailing technologies and adoption obstacles in maritime logistics - Annika Wohlleber; Christopher Münch; Evi Hartmann (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: Digital technologies (DTs) are transforming logistics operations in the shipping industry. Yet, the industry is only in the early stages of digitalization. Consequently, there is a lack of empirical evidence on applied DTs and related obstacles for DT adoption. Methodology: A multiple case study was conducted comprising ports, freight forwarders, and carriers. Based on 18 expert interviews and additional data sources, differences and similarities concerning currently applied DTs and associated obstacles to DT adoption were examined. Findings: Presented findings indicate comprehensive efforts toward a paperless and digitalized way of operating within maritime container logistics (MCL) by using DTs such as blockchain, cloud solutions, and artificial intelligence. Especially ports strive to achieve collaborative data usage but are frequently hindered by a lack of inter-organizational data sharing. Furthermore, the inherent complexity of the MCL chain and employees' and managers' defensiveness toward technological change needs to be overcome by applying suitable measures for DT adoption. Originality: The research contributes to the scarce literature of DT adoption within MCL by providing empirical insights into the state-of-the-art of DTs for ports, freight forwarders, and carriers. Additionally, this research is the first to address implications for tackling existing obstacles for successful DT adoption in MCL.
urn:nbn:de:gbv:830-882.0201067; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; Maritime Logistics